Central corneal thickness and intraocular pressure in patients of primary open angle glaucoma and normal population in Nepalese population: A hospital based study - Agarwal, Lalit; Agrawal, Nisha; Badhu, Badri Prasad; Lavaju, Poonam (Nepalese Journal of Ophthalmology, 2019)
Introduction: Central corneal thickness (CCT) is a powerful predictor of primary open angle glaucoma. Individualized risk assessment is critical for early diagnosis and management of glaucoma. Objectives: To compare CCT and intraocular pressure in patients of primary openangle glaucoma (POAG) with those of normal population. Materials and methods: A Comparative Cross-Sectional Study was performed in Ophthalmology department of B. P. Koirala Institute of Health Sciences, Nepal. Newly diagnosed cases of primary glaucoma (open angle, normal tension) of 18 years and above, without known systemic diseases were included. Results: Out of a total of 291 subjects (582 eyes), 105 subjects (210 eyes) were with primary glaucoma and 186 (382 eyes) were normal subjects. There was no significant difference in CCT between glaucomatous (533.57 μm) and normal (530.06 μm) eyes (p=0.1). Cornea was thinner (518.±18.03 μm) in eyes with severe glaucomatous damage (cup:disc ratio > 0.8) than in moderate glaucomatous damage (cup:disc ratio=0.5-0.8)(p=0.003). There was a statistically significant difference of 22.05 μm in CCT between POAG and NTG (p<0.001). A positive correlation was found between IOP & CCT in both cases and control group (p=0.000; r = 0.355, 0.254; r2 =0.126, 0.064 respectively). Conclusion: Majority of studied Nepalese population have CCT less than 550 μm, thus increasing the risk of POAG. CCT decreases with age, and females with glaucoma have significantly thicker cornea than men. There is a significant positive correlation between CCT and IOP, and IOP will have to be adjusted for CCT for proper diagnosis and monitoring of glaucomatous damage in Nepalese population too.